Tetraethylthiuram disulphide alleviates pulmonary fibrosis through modulating transforming growth factor-β signalling. (December 2021) - Jiang, Hongchao; Zhao, Yaxue; Tang, Huirong; Duan, Shixin; Li, Mengkai; Yang, Xinyi; Liu, Jingting; Lou, Xinyi; Cai, Yuanyuan; Zhao, Wenjuan; Sun, Lei; Qian, Feng
Abstract: Idiopathic pulmonary fibrosis (IPF) induces significant morbidity and mortality, for which there are limited therapeutic options available. Here, we found that tetraethylthiuram disulphide (disulfiram, DSF), a derivative of thiuram, used in the treatment of alcohol abuse, has an inhibitory effect on bleomycin (BLM)-induced pulmonary fibrosis via the attenuation of the fibroblast-to-myofibroblast transition, migration, and proliferation of fibroblasts. Furthermore, DSF inhibited the activation of primary pulmonary fibroblasts and fibroblast cell line under transforming growth factor-β 1 (TGF-β1) challenge. Mechanistically, the anti-fibrotic effect of DSF on fibroblasts depends on the inhibition of TGF-β signalling. We further determined that DSF interrupts the interaction between SMAD3 and TGF-β receptor Ι (TBR Ι), and identified that DSF directly binds with SMAD3, in which Trp326, Thr330, and Cys332 of SMAD3 are critical binding sites for DSF. Collectively, our results reveal a powerful anti-fibrotic function of DSF in pulmonary fibrosis through the inhibition of TGF-β/SMAD signalling in pulmonary fibroblasts, indicating that DSF is a promising therapeutic candidate for IPF. Graphical Abstract: ga1 Highlights: Disulfiram ameliorates bleomycin-induced pulmonary fibrosis. Disulfiram inhibits the functions of pulmonary fibroblasts both in vivo and in vitro . Disulfiram inhibited TGF-β/SMAD signalling in fibroblasts by disrupting the interaction of SAMD3 and TGF-β receptor.